EMPLOYEE TRANSFER STRATEGY, CASE STUDY: PT KERETA API INDONESIA (PERSERO) HEAD OFFICE - Maritza Amalia Puteri Hadi; Muhammad Saddam Sofyandi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Employee transfer is an important human resource management practice in large organizations, yet its implementation often presents managerial and employee-related challenges. In state-owned enterprises, transfer strategies are intended to support organizational needs and employee career development, but empirical evidence on how these strategies operate in practice remains limited. This study examines the employee transfer strategy at the Head Office of PT Kereta Api Indonesia (Persero). Using a qualitative case study approach, data were collected through in-depth interviews with two human resource personnel and five transferred employees, supported by document analysis. Data credibility was ensured through triangulation, and thematic analysis was applied to interpret the findings. The results indicate that employee transfer strategies are formulated based on organizational needs, employee competencies, and career development considerations, and are implemented through structured administrative procedures and performance-based evaluations. However, challenges persist related to communication clarity and alignment between policy and practice. The study contributes to human resource management literature by positioning employee transfer as a dynamic strategic process rather than a purely administrative mechanism, particularly within state-owned enterprises, and offers practical insights for improving transfer effectiveness.